Anthropological materials from burial № 4 of the Kulikovo mound - O.A. Kalmina; D.S. Ikonnikov; O.V. Kalmin; R.E. Golovin; O.O. Kalmin (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2024)
Background. The study of anthropological materials of people of distant historical epochs is an important source of information about the lifestyle, culture and state of medicine in antiquity. The study of anthropological materials of people of distant historical epochs is an important source of information about the lifestyle, culture and state of medicine in antiquity. The purpose of the work is to reconstruct the morphological characteristics of the individual of the Bronze Age and the character his the physical stress in the process of life. Materials and methods. The work introduces the results of the complex study of anthropological materials from burial № 4 of burial mound I of the Kulikovo group of burial mounds (Republic of Mordovia, the territory of the urban district of Saransk). Materials are consist of the skull, right pelvic bone, and right and left femurs. All bones show marked post-mortem destruction. The facial skeleton of the skull is destroyed. The study of anthropological materials was carried out visually and metrically. The measurements were carried out in accordance with the generally accepted method of R. Martin. Results. During the study, anthropological materials were carefully examined and measured. The proportions of the skull and the length of the individual’s body were determined. Traces of pathological changes and the indicators of mechanical stress were traced on many bones. A bilateral pathology “cribra orbitalia” was found on the skull. The occipital bone showed the trace of manifestatio proatlantis. Signs of gonarthrosis and traces of inflammatory processes are found on the femur bones. Conclusion. The examined skeleton, could belong to a woman of 35-45 years old. The length of the individual’s body was approximately 160.5 cm. Traces of multiple pathological changes and indicators of mechanical stress were traced on the skull and bones of the postcranial skeleton. Many of them are the result of intense physical activity of the individual.